A Church Undone : Documents from the German Christian Faith Movement, 1932-1940 - Solberg, Mary M.; Solberg, Mary M. (Book collections on Project MUSE., 2015)
Decades after the Holocaust, many assume that the churches in Germany resisted the Nazi regime. In fact, resistance was exceptional. Almost all Germans were Christians, and almost all Christians in Germany stood by, becoming intentionally or unintentionally complicit in Nazi policies and practices. In the early 1930s, a movement emerged within German Protestantism with the aim of fully integrating Nazi ideology, German national identity, and Christian faith. The Deutsche Christen or, "German Christians," as they were called, interpreted the Christian faith and the role of the church in society in service of the Nazi revolution. They married centuries-old Christian anti-Judaism to the Nazis' racial antisemitism and sought to eradicate all traces of Judaism from Christianity. The "German Christian" publication program, designed to advance their ideology, included books and pamphlets, radio talks and speeches, as well as liturgies and retranslations of Scripture. For the first time in English, Mary M. Solberg presents a selection of representative documents of the "German Christians." Her introduction to the volume sets the historical context of the movement and offers short introductions to each of the specific readings. The collection includes key responses critical of the German Christians by Karl Barth and Dietrich Bonhoeffer, among others.